Chapter 17 - TGFβ and Signaling through Receptor Serine/Threonine Protein Kinases - IJsbrand M. Kramer (Signal Transduction, 2016)
This chapter deals with serine/threonine kinase receptors which basically are members of the TGFβ-receptor family. We place the subject in the context of epidermal–mesenchymal transition, immunosurveillance, and the Spemann organizer (development). We list the members of the TGFβ family (ligands), their traps, and their accessory receptors. We detail the activation mechanism of TGFβ receptors, formation of type-1 and type-2 receptor dimers, how phosphorylation of the GS domain removes an inhibitory wedge from the N-lobe, and how this leads to phosphorylation of receptor-regulated SMAD proteins. We describe the SMAD proteins, including domains, structure, phosphorylation, and ubiquitinylation sites, and how they form heterotrimeric complexes that bind DNA. We show how they recruit co-activators and contribute to the assembly of the transcription pre-initiation complex and how linker-phosphorylation and subsequent ubiquitinylation plays a role in terminating their action. We show how TRIM33 and cell lineage-dependent (or master) transcription factors prepare the road for SMADS and how they determine cell-specific cell responses.